Micronodular thymoma with lymphoid stroma: Contrast-enhanced CT features with histopathological correlation in 10 patients - Miao, Lei; Yang, Lin; Zhang, Jia-Xing; Sun, Xu-Jie; Zhang, Huan-Huan; Qi, Lin-Lin; Li, Meng (Frontiers in Oncology, 2022)
Objectives The aim of this study was to evaluate and summarize the contrast-enhanced computed tomography (CECT) imaging features of MTWLS based on all MTWLS patients at our institution, as the first imaging study of MTWLS worldwide. Methods This retrospective study included 10 MTWLS patients who underwent CECT between April 2012 and November 2021. We collected and analysed CECT imaging features, including location, size, shape, tumour density classification, and CT value of the solid component. Descriptive statistical analysis was performed using SPSS software (version 26.0; IBM). Results Ten patients (5 males [50%], 5 females [50%]; median age, 61.4 years; range, 54-72 years) underwent CECT. Of the 10 cases, 1 was pure cystic, 7 were cystic-solid, and 2 were pure solid. Among the solid or cystic-solid cases, the mean CT value of the measurable solid component on the enhanced scan was 93.89 HU: 2 showed moderate enhancement, 7 showed significant enhancement, and all 9 masses were adjacent to the mediastinal pleura, pericardium, or large vessels. Additionally, 6 cases were round/oval in shape, and 4 were irregularly shaped. There were no malignant tumour signs, including penetration of the mediastinal pleura or involvement of the pericardium, pleural effusion, diaphragm elevation, or direct vascular invasion, in any patient. Conclusion MTWLS demonstrates certain features on CT, such as a high cystic change rate, significant solid component enhancement, and no malignant, invasive imaging features. These CT features are helpful for diagnosing MTWLS.